2016
DOI: 10.1021/acs.langmuir.6b00462
|View full text |Cite
|
Sign up to set email alerts
|

Self-Generated Electrokinetic Fluid Flows during Pseudomorphic Mineral Replacement Reactions

Abstract: Pseudomorphic mineral replacement reactions involve one mineral phase replacing another, while preserving the original mineral's size and texture. Macroscopically, these transformations are driven by system-wide equilibration through dissolution and precipitation reactions. It is unclear, however, how replacement occurs on the molecular scale and what role dissolved ion transport plays. Here, we develop a new quantitative framework to explain the pseudomorphic replacement of KBr crystal in a saturated KCl solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…The high-resolution 3D dataset of the temporal evolution of KBr-KCl replacement reaction with X-CT allows key observations in order to refine our understanding about how much porosity develops during the replacement, how porosity is distributed over time, and how the reaction front progresses into the crystal. These quantitative observations complement previous works (Kar et al, 2016;Raufaste et al, 2010) and allow us to better understand the dynamics of the replacement propagation and associated mechanisms, such as volume change, porosity geometry and transport regime. By comparing two sets of experiments that mimic two different environments for fluid-rock interactions (single event versus intermittent flow), the phenomenon we describe and quantify can ultimately be transferred to other natural systems.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The high-resolution 3D dataset of the temporal evolution of KBr-KCl replacement reaction with X-CT allows key observations in order to refine our understanding about how much porosity develops during the replacement, how porosity is distributed over time, and how the reaction front progresses into the crystal. These quantitative observations complement previous works (Kar et al, 2016;Raufaste et al, 2010) and allow us to better understand the dynamics of the replacement propagation and associated mechanisms, such as volume change, porosity geometry and transport regime. By comparing two sets of experiments that mimic two different environments for fluid-rock interactions (single event versus intermittent flow), the phenomenon we describe and quantify can ultimately be transferred to other natural systems.…”
Section: Introductionsupporting
confidence: 81%
“…in Kondratiuk et al, 2015). The KBr-KCl replacement exhibits an elongated anisotropic porosity that controls the replacement propagation (Kar et al, 2016;Raufaste et al, 2010). Fluid flow can extend pores to create the elongated structures (Kar et al, 2015;Raufaste et al, 2010), which are similar to finger pipes observed in nature during dissolution (Szymczak and Ladd, 2009).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…is consistent with the determined value of E a and the Avrami exponential n-value, and emphasizes the importance of the porosity generation in mineral replacement processes. The study provides data for future work on determining the mechanism of ion transport through micropores, notably the recent discussions on the role of charge gradients in small pores in enhancing transport by diffusioosmosis (Kar et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The stability of these fronts [ Kondratiuk et al , ] will be investigated in future work. Interestingly, recent studies [ Raufaste et al , ; Kar et al , ] report fingering at a microscopic scale (∼100 μm), presumably connected with self‐generated convective flows by the process of diffusion osmosis [ Kar et al , ; Ajdari and Bocquet , ].…”
Section: Discussionmentioning
confidence: 99%